Easily Regenerable Solid Adsorbents Based on Polyamines for Carbon Dioxide Capture from the Air. Issue 5 (18th March 2014) - Goeppert, Alain; Zhang, Hang; Czaun, Miklos; May, Robert B.; Prakash, G. K. Surya; Olah, George A.; Narayanan, S. R.
Abstract Adsorbents prepared easily by impregnation of fumed silica with polyethylenimine (PEI) are promising candidates for the capture of CO2 directly from the air. These inexpensive adsorbents have high CO2 adsorption capacity at ambient temperature and can be regenerated in repeated cycles under mild conditions. Despite the very low CO2 concentration, they are able to scrub efficiently all CO2 out of the air in the initial hours of the experiments. The influence of parameters such as PEI loading, adsorption and desorption temperature, particle size, and PEI molecular weight on the adsorption behavior were investigated. The mild regeneration temperatures required could allow the use of waste heat available in many industrial processes as well as solar heat. CO2 adsorption from the air has a number of applications. Removal of CO2 from a closed environment, such as a submarine or space vehicles, is essential for life support. The supply of CO2‐free air is also critical for alkaline fuel cells and batteries. Direct air capture of CO2 could also help mitigate the rising concerns about atmospheric CO2 concentration and associated climatic changes, while, at the same time, provide the first step for an anthropogenic carbon cycle.